1991
DOI: 10.1007/bf01726452
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of regional lymphadenitis following BCG vaccination

Abstract: In this study we presented 92 cases with regional lymphadenitis (over 1 cm in diameter) which was caused by BCG vaccination generally performed a few days after birth. The patients were divided into four therapy groups. In group I, the lymphadenitis in 26 cases was excised totally by a surgical operation and they improved in a median period of four weeks (average: 4.4). No therapy was applied in 33 patients constituting group II and their periods of improvement were 28 weeks (average: 29.1). Sixteen cases in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Studies have clearly demonstrated that there is no difference between various conservative treatments and with no treatment at all [15,16]: Spontaneous regression occurs in 62% and 67%, respectively. The inflammatory process, however, proceeds when the attacked lymph node has reached a certain size, and perforation and fistulation occur in at least 40%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have clearly demonstrated that there is no difference between various conservative treatments and with no treatment at all [15,16]: Spontaneous regression occurs in 62% and 67%, respectively. The inflammatory process, however, proceeds when the attacked lymph node has reached a certain size, and perforation and fistulation occur in at least 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Although all tubercle bacilli were isoniazid-sensitive, conservative measures failed in the presence of advanced adenitis. Surgery was the treatment of choice for these fluctuant, enlarged lymph nodes, where the inflammatory process had even infiltrated or perforated the skin [11,15,16]. With a relapse rate of 14% and the risk of fistulation, needle aspiration of pus was not an alternative to surgery [11,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical indications for the management of BCG vaccine-induced regional suppurative lymphadenitis need to be defined so far [ 17 , 23 ]. Based on the literature review and our experience, hereby, we propose the indications for surgical management as follows: the enlarged lymph node greater than 1 cm in size [ 9 ] and ultrasonography revealing liquefaction and capsule penetration of the lymph node(s); rapidly enlarging or infiltrating nodes [ 22 ]; infiltrating overlying skin [ 10 , 21 , 22 ]; spontaneously perforated or sinus formation [ 10 , 19 , 21 ]; fixation of regional lymph node(s) [ 14 ]; lymph nodes larger than 1.5–3 cm [ 10 , 19 , 21 ]; mass lasting for 3 to 6 months without regression [ 15 , 19 ]; or repeated collections after needle aspiration, especially with matted and multilocular nodes [ 17 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgical management of BCG vaccine-induced suppurative lymphadenitis has been reported with good results [ 9 , 18 , 25 ], the disadvantages are the exposure of sedation or general anesthesia, potential intra- and post-operative complications [ 3 , 17 ], and reoccurrence due to residual adenopathy with sinus formation requiring more than one procedure [ 26 ]. Nevertheless, surgical excision, as an invasive technique, still needs to balance the risks of general anesthesia and potential surgical complications.…”
Section: Discussionmentioning
confidence: 99%